XPS investigation of monatomic and cluster argon ion sputtering of tantalum pentoxide - Simpson, Robin; White, Richard G.; Watts, John F.; Baker, Mark A. (Applied surface science, 2017)
•Ion beam induced oxide reduction from monatomic and gas cluster ion beam exposure are compared.•Lower relative level of preferential sputtering is shown in gas cluster ion beam depth profiling.•A lack of “steady state” is observed in gas cluster ion beam depth profiles of tantalum pentoxide.•Possible mechanisms behind the observed results, including temperature effects are proposed. In recent years, gas cluster ion beams (GCIB) have become the cutting edge of ion beam technology to sputter etch organic materials in surface analysis. However, little is currently known on the ability of argon cluster ions (Arn+) to etch metal oxides and other technologically important inorganic compounds and no depth profiles have previously been reported. In this work, XPS depth profiles through a certified (European standard BCR-261T) 30nm thick Ta2O5 layer grown on Ta foil using monatomic Ar+ and Ar1000+ cluster ions have been performed at different incident energies. The preferential sputtering of oxygen induced using 6keV Ar1000+ ions is lower relative to 3keV and 500eV Ar+ ions. Ar+ ions exhibit a steady state O/Ta ratio through the bulk oxide but Ar1000+ ions show a gradual decrease in the O/Ta ratio as a function of depth. The depth resolution and etch rate is substantially better for the monatomic beam compared to the cluster beam. Higher O concentrations are observed when the underlying Ta bulk metal is sputtered for the Ar1000+ profiles compared to the Ar+ profiles.